THE GREAT COMMANDER WHO WAS BORN IN ANDIJAN (ResearchJet Journal of Analysis and Inventions, 2021)
In this article Zakhiriddin Mukhammad Bobur, a descendant of Amir Temur, was born in Andijan. He was forced to rule the whole Fergana state from an early age and the founding of a great state and Boburi dynasty in India.